Nurses' Knowledge of Hospital Safety in A Tertiary Healthcare Setting - Athirarani M․R․; Ajayan Kamalasanan; Vinoth Raman; Jibina John; Lekshmi R․; Liji C․; Preetha S․; Rejani A․V․; Reshma S․R․; Roshni K․P․ (Next Research, 2025)

Comparative investigation of structural properties and biological applications of chemical and biogenic synthesis of zirconium dioxide (ZrO2) nanoparticles using Passiflora edulis - Preetha S; Anilkumar P; Nisha Jenifar A (Journal of Photochemistry and Photobiology B: Biology, 2025)

Identification and comparative analysis of differential proteins expression in rice under biotic stress by protein sequencing - Subhashini Shinde; P. S. Abida; Manjesh Saakre; Haseena Bhaskar; R. Beena; R. Preetha (Cereal Research Communications, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

Cryopreservation of shoot meristems of Baliospermum montanum (Willd.) Muell. Arg. for long-term conservation and sustainable utilization - K. P. Parvathi; T. S. Preetha; A. S. Hemanthakumar (Vegetos, 2023)

Discovery of novel microRNAs and their pathogenic responsive target genes in mild traumatic brain injury - Saurav Bhowmick; M. R. Preetha Rani; Shubham Singh; P. M. Abdul-Muneer (Experimental Brain Research, 2023)

Implementation and operational feasibility of an offshore floating charging station for sustainable marine transportation - V. Sruthy; P. K. Preetha (Environment, Development and Sustainability, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Phosphorus fractions in the sediment of a tropical reservoir, India: Implications for pollution source identification and eutrophication - Ajoy Saha; P. K. Jesna; V. L. Ramya; S. Sibina Mol; Preetha Panikkar; M. E. Vijaykumar; U. K. Sarkar; B. K. Das (Environmental Geochemistry and Health, 2022)

Quantifying Surface Water and Ground Water Interactions using a Coupled SWAT_FEM Model: Implications of Management Practices on Hydrological Processes in Irrigated River Basins - Pooja P. Preetha; Naveen Joseph; Balaji Narasimhan (Water Resources Management, 2021)

Evaluation of Spatio-temporal Changes in Surface Water Quality and Their Suitability for Designated Uses, Mettur Reservoir, India - Ajoy Saha; V. L. Ramya; P. K. Jesna; S. Sibina Mol; Preetha Panikkar; M. E. Vijaykumar; U. K. Sarkar; B. K. Das (Natural Resources Research, 2021)

A Methodical Assessment of Floodplains in Mixed Land Covers Encompassing Bridges in Alabama State: Implications of Spatial Land Cover Characteristics on Flood Vulnerability - Pooja P. Preetha; Niloufar Shirani-bidabadi; Ashraf Z. Al-Hamdan; Michael Anderson (Water Resources Management, 2021)

Integrating finite-element-model and remote-sensing data into SWAT to estimate transit times of nitrate in groundwater - Pooja P. Preetha; Ashraf Z. Al-Hamdan (Hydrogeology Journal, 2020)

Multi-level pedotransfer modification functions of the USLE-K factor for annual soil erodibility estimation of mixed landscapes - Pooja P. Preetha; Ashraf Z. Al-Hamdan (Modeling Earth Systems and Environment, 2019)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Investigating the effects of environmental factors on autism spectrum disorder in the USA using remotely sensed data - Ashraf Z. Al-Hamdan; Pooja P. Preetha; Reem N. Albashaireh; Mohammad Z. Al-Hamdan; William L. Crosson (Environmental Science and Pollution Research, 2018)

Trends and variability of meteorological drought over the districts of India using standardized precipitation index - P Guhathakurta; Preetha Menon; P M Inkane; Usha Krishnan; S T Sable (Journal of Earth System Science, 2017)

Modelling the food web for assessment of the impact of stock supplementation in a reservoir ecosystem in India - M. F. Khan; P. Preetha; A. P. Sharma (Fisheries Management and Ecology, 2015)
Comparative estimates of trophic status and energy flow were carried out in a tropical reservoir ecosystem in India to assess the impact of fish stocking. Mass‐balanced models of the reservoir ecosystem were constructed for two periods – 1982–1983 and 2002–2003 – using ecopath software to determine the impacts on different groups before and after stocking. Mixed trophic impact ( MTI ) analyses indicated that phytoplankton and detritus have a positive impact on most groups. There was a decrease in nutrient flow through the system from pre‐stocking to post‐stocking (22.28%). The baseline was higher by 0.29% in the post‐stock phase indicating maturity. The ecosystem indices tested indicate that the reservoir was in a more resilient state post‐stocking than during the pre‐stocking phase. The ‘health’ of the ecosystem showed an improvement, which indicates a positive impact of stocking.

Characterizing trophic interactions of a catfish dominated tropical reservoir ecosystem to assess the effects of management practices - Preetha Panikkar; M. Feroz Khan; V. R. Desai; N. P. Shrivastava; A. P. Sharma (Environmental Biology of Fishes, 2015)

Parmotrema tinctorum exhibits antioxidant, antiglycation and inhibitory activities against aldose reductase and carbohydrate digestive enzymes: an in vitro study - P. Salin Raj; A. Prathapan; Jomon Sebastian; Antu K. Antony; Mariam Philip Riya; M.R. Preetha Rani; H. Biju; S. Priya; K.G. Raghu (Natural Product Research, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Diazotrophic diversity in the rhizosphere of two exotic weed plants, Prosopis juliflora and Parthenium hysterophorus - B. Cibichakravarthy; R. Preetha; S. P. Sundaram; K. Kumar; D. Balachandar (World Journal of Microbiology and Biotechnology, 2012)

Studies on toxicity of antitubercular drugs namely isoniazid, rifampicin, and pyrazinamide in an in vitro model of HepG2 cell line - Meenakshi Singh; Preetha Sasi; Gaurav Rai; Vinod H. Gupta; Deepak Amarapurkar; Pramod P. Wangikar (Medicinal Chemistry Research, 2011)

Protective role of sulphated polysaccharides in abating the hyperlipidemic nephropathy provoked by cyclosporine A - Anthony Josephine; Coothan Kandaswamy Veena; Ganapathy Amudha; Sreenivasan P. Preetha; Palaninathan Varalakshmi (Archives of Toxicology, 2007)

Evaluating the Effect of Sulphated Polysaccharides on Cyclosporine A Induced Oxidative Renal Injury - Anthony Josephine; Coothan Kandaswamy Veena; Ganapathy Amudha; Sreenivasan P. Preetha; Palaninathan Varalakshmi (Molecular and Cellular Biochemistry, 2006)

Effect of increasing duration of diabetes mellitus type 2 on glycated hemoglobin and insulin sensitivity - Meena Verma; Sangeeta Paneri; Preetha Badi; P. G. Raman (Indian Journal of Clinical Biochemistry, 2006)